2018
DOI: 10.1080/19336950.2018.1532255
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels in the sinoatrial node and their role in heart rate control

Abstract: Potassium currents determine the resting membrane potential and govern repolarisation in cardiac myocytes. Here, we review the various currents in the sinoatrial node focussing on their molecular and cellular properties and their role in pacemaking and heart rate control. We also describe how our recent finding of a novel ATP-sensitive potassium channel population in these cells fits into this picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 117 publications
(144 reference statements)
0
21
0
Order By: Relevance
“…The most prominent feature was the temporary arrest of synchronous beating (Fig. 5), reminding us of the amplitude death of coupled oscillators [49][50][51] and sinus arrest of in vivo hearts [52][53][54] . Its mechanism seemed to be hidden in the momentary arrests of the CSs that appeared as its precursors.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent feature was the temporary arrest of synchronous beating (Fig. 5), reminding us of the amplitude death of coupled oscillators [49][50][51] and sinus arrest of in vivo hearts [52][53][54] . Its mechanism seemed to be hidden in the momentary arrests of the CSs that appeared as its precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Yanni et al (68) showed that in aged mice there is an increase in the area of the SAN that lacks the relatively TTX-resistant Na V 1.5 sodium channel isoform and yet an increased effect of 2 μM TTX on firing rate, possibly reflecting an upregulation of TTX-sensitive Na + channel isoforms. K + currents.-There are clear roles for voltage-gated, Ca 2+ -activated, and inward rectifier K + channels in the repolarization and diastolic depolarization phases of the SAN AP (93)(94)(95)(96)(97)(98). The delayed rectifier K + channels K V 7.1 (KCNQ1), which underlies I Ks , and K V 11.1 (ERG), which produces I Kr , are thought to be primarily responsible for repolarization of the sinoatrial AP.…”
Section: Overview Of Age-dependent Changes In Ionic Currents In Sinoatrial Node Myocytesmentioning
confidence: 99%
“…The relative lack of information about K + currents in SAMs is particularly important for aging because the AP prolongation along with reduced Ca 2+ current density predicts a decrease in K + currents in aged SAMs (10,11,13). Although, as discussed above, K + currents play an important role in determining cycle length through modulation of multiple AP waveform parameters and are implicated in SND (95,(97)(98)(99)(100)103), there is no information to our knowledge about age-dependent changes in K + currents in SAMs.…”
Section: Limitations Gaps In Knowledge and Future Directionsmentioning
confidence: 99%
“…This cardiac impulse in the SAN is initially mediated by a sodium influx via hyperpolarization-activated cyclic nucleotide-gated cation channels (HCN1, 2, and 4). Thereafter, depolarization occurs progressively via T-type calcium channels (Cav3.1 and 3.2), and L-type calcium channels (Cav1.2 and 1.3) 2,3 . Repolarization of the cardiac action potential occurs via the inactivation of L-type calcium currents and the opening of potassium channels, such as IKr (Kv11.1/hERG) and IKs (KCNQ1/KvLQT1) in the SAN.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these key ion channels, the messenger RNA (mRNA) expression levels of acetylcholine-activated K+ current, IKACh (Kir3.1 and 3.4), and sodium-calcium exchanger 1 (NCX1) are also known to regulate the cardiac action potential 3 .…”
Section: Introductionmentioning
confidence: 99%